FEATURES AND CHALLENGES OF FORMING FINANCIAL MECHANISMS FOR THE DEVELOPMENT OF TERRITORIAL COMMUNITIES IN UKRAINE - SOROKA, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the features and challenges of forming financial mechanisms for the development of territorial communities in Ukraine. The study analyzes the legislative framework regulating financial activities of local communities, evaluates the efficiency of financial resource utilization, and examines opportunities for attracting additional funding sources. The research identifies key obstacles to achieving financial self-sufficiency for territorial communities and proposes strategies for overcoming them. The research highlights the legal framework governing financial mechanisms, including the Budget Code of Ukraine, the Law on Local Self-Government, and the Law on Voluntary Association of Territorial Communities. A critical challenge for communities is the effective use of financial resources. The study identifies inefficiencies in budget planning, lack of transparency in expenditures, and limited access to alternative financing, such as investments and public-private partnerships. Addressing these issues requires expanding the local tax base, enhancing financial literacy among local officials, promoting public-private cooperation, and increasing citizen engagement in budgetary processes. The findings suggest that improving financial mechanisms will enhance the sustainability of territorial communities and contribute to balanced regional development. Strengthening financial autonomy through strategic reforms is essential for ensuring economic resilience and sustainable growth of Ukrainian communities.